Farmer Group Performance Bali Cattle In Luwu District East : The Economic Analysis - Supardi Rusdiana; Soeharsono Soeharsono (The Faculty of Veterinary Medicine of Syiah Kuala University, 2017)
This research was conducted in the District Mangko Tano East Luwu in South Sulawesi Province, in 2017. The area of research is supported by oil palm plantations, palm plantations, agricultural land, forestry land, vacant land that has not been explored by farmers and other vacant land. The study was conducted by the method of field survey, according to information from the local Animal Husbandry Department, the criteria in the data is the cattle population in farmer.The purpose of this study was to determine the economic analysis on a group of cattle ranchers. Primary data and secondary data were analyzed using descriptive tabulation, quantitatively and economically. The results of the research effort shows that beef cattle, ranchers group profit amounted Rp.3.637.500/year, Agung Sindo Village B/C ratio of 1.2, Kalaenaliri village of Rp.3.886.000/ year ratio B/C 1.2, and the Wanasari Village of Rp.3.788.000/year and ratio of B/C 1.2. Forage in locations very research support to the development of beef cattle Bali. But farmers are accustomed way of raising beef cattle between 2-4 head/breeder, so it needs additional maintenance business scale between 5-10 cattle/livestock farmers, so that the business more effectively and efficiently and economically will benefit farmers.